2010
DOI: 10.1007/s11626-010-9364-5
|View full text |Cite
|
Sign up to set email alerts
|

The effects of platelet-rich plasma derived from human umbilical cord blood on the osteogenic differentiation of human dental stem cells

Abstract: Platelet-rich plasma (PRP) is an emerging therapeutic application because PRP contains various growth factors that have beneficial effects on tissue regeneration and engineering. Mesenchymal stem cells and PRP derived from peripheral blood have been well studied. In this study, we investigated the effects of PRP derived from human umbilical cord blood (UCB-PRP) on proliferation, alkaline phosphatase (ALP) activity, and osteogenic differentiation of stem cells from human exfoliated deciduous teeth (SHEDs), dent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 24 publications
(33 reference statements)
3
39
1
Order By: Relevance
“…It contains a pool of endogenous growth factors such as; TGF-b, PDGF, FGF and IGF, which enhances the expansion of MSCs (Sotiropoulou, Perez, Salagianni, Baxevanis, & Papamichail, 2006). Few studies have demonstrated the positive effects of human PL (PRP) on the proliferation and mineralized differentiation of other types of MSCs like human dental stem cells, dental pulp stem cells (DPSCs) (Lee et al, 2011) and periodontal ligament stem cells (PDLSCs) (Lee et al, 2011). In this study, proliferation rates were variable among different concentrations of PL for both DPSCs and SCAP, when compared with FBS.…”
Section: Discussionmentioning
confidence: 99%
“…It contains a pool of endogenous growth factors such as; TGF-b, PDGF, FGF and IGF, which enhances the expansion of MSCs (Sotiropoulou, Perez, Salagianni, Baxevanis, & Papamichail, 2006). Few studies have demonstrated the positive effects of human PL (PRP) on the proliferation and mineralized differentiation of other types of MSCs like human dental stem cells, dental pulp stem cells (DPSCs) (Lee et al, 2011) and periodontal ligament stem cells (PDLSCs) (Lee et al, 2011). In this study, proliferation rates were variable among different concentrations of PL for both DPSCs and SCAP, when compared with FBS.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been demonstrated that PRP acts as a powerful medium supporting various growth factors in the culture of different kinds of cells, including MSCs, fibroblasts, dental stem cells, and osteoblasts (Shengyun et al 2012). Lee et al (2011) showed an increase in growth and differentiation of PRP-treated periodontal ligament cells and stromal stem cells as type I collagen gene expression (Lee et al 2011). In addition, the growth factors in PRP have a supportive role in cell migration, proliferation, and differentiation; all are critical for wound healing and soft-tissue augmentation.…”
Section: Discussionmentioning
confidence: 99%
“…36 Deciduous teeth and adult molars were obtained from the Seoul National University Dental Hospital after securing the approval of the institutional review board at Seoul National University Dental Hospital. The deciduous teeth and adult molars were put into Hank's balanced salt solution (Welgene, Dae-gu, Korea) supplemented with 3% antibiotic-antimycotic solution (Life Technologies, Carlsbad, CA) at 4°C.…”
Section: Cell Culture and H 2 O 2 Treatmentmentioning
confidence: 99%